2014
DOI: 10.1016/j.bbi.2013.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bovine colostrum supplementation on upper respiratory illness in active males

Abstract: 23Bovine colostrum (COL) has been advocated as a nutritional countermeasure to 24 exercise-induced immune dysfunction and increased risk of upper respiratory illness 25 (URI) in athletic populations, however, the mechanisms remain unclear. During winter 26 months, under double-blind procedures, 53 males (mean training load ± SD, 50.5 ± 27 28.9 MET-hweek -1 ) were randomized to daily supplementation of 20 g of COL (N = 28 25) or an isoenergetic/isomacronutrient placebo (PLA) (N = 28) for 12 weeks. Venous 29 bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(110 citation statements)
references
References 53 publications
4
105
1
Order By: Relevance
“…Although there was no effect on the summed response, there were clear differences at the lowest dose and increased sensitivity in the COL group. Taken together this supports previous evidence from our laboratory where COL has been shown to act as a nutritional countermeasure to the decreased immunity (and increased susceptibility to illness) following prolonged exercise( 1,2) .…”
Section: Resultssupporting
confidence: 79%
“…Although there was no effect on the summed response, there were clear differences at the lowest dose and increased sensitivity in the COL group. Taken together this supports previous evidence from our laboratory where COL has been shown to act as a nutritional countermeasure to the decreased immunity (and increased susceptibility to illness) following prolonged exercise( 1,2) .…”
Section: Resultssupporting
confidence: 79%
“…However, we have undertaken a number of studies on various immune markers and, on average, have observed a large effect (Cohen's d = 1.25) with the dosage of bovine colostrum used in the present study (e.g., [18,19,26]). To detect such a magnitude of effect in this study, a sample size of n = 15 per group (n = 30 in total) is required to provide > 90% power.…”
Section: Discussionmentioning
confidence: 99%
“…The previous findings of no inhibitory effect of prolonged exercise on skinfold responses to the irritant, croton oil, provide evidence that in the context of DPCP, responses are dependent on cell-mediated events rather than local inflammatory processes [15]. Given that a recent meta-analysis [16] of five randomised controlled trials (including one from our laboratory) of COL supplementation showed a reduction in the incidence of URS during exercise training [26,[32][33][34], it is likely that an increase in recall sensitivity provides a mechanistic explanation for reduced URS. It will be useful, however, for future studies to monitor URS in the period following DPCP sensitisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular ingestion of bovine colostrum may also limit the increase in gut permeability caused by prolonged strenuous exercise and reduce the risk of developing heat stroke 50 . Several studies have also reported that daily oral bovine colostrum supplementation reduces the total number of days with self-reported URS 48,[51][52][53] , the incidence of URS episodes 48,[51][52][53][54] and duration of self-reported URS episodes 51,53 in adults involved in exercise training.…”
Section: Colostrummentioning
confidence: 99%